2009
DOI: 10.1186/1471-2296-10-19
|View full text |Cite
|
Sign up to set email alerts
|

Primary care physicians' reported use of pre-screening discussions for prostate cancer screening: a cross-sectional survey

Abstract: Background: Professional medical organizations recommend individualized patient decision making about prostate cancer screening. Little is known about primary care physicians' use of prescreening discussions to promote informed decision making for prostate cancer screening. The aim of this study is to explore physicians' use of pre-screening discussions and reasons why physicians would or would not try to persuade patients to be screened if they initially refuse testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 10 publications
3
41
0
Order By: Relevance
“…The study, which included 35 FP physicians and 28 general internists, reported that 79% of PCPs engaged in prescreening discussions with their patients. 10 Our findings also showed that 64.1% (representing 56,137 nationally) of PCPs that engage in discussions reported that their usual policy when discussing PSA testing with patients was to talk the patient into getting the PSA test. In a qualitative study, researchers divided U.S. PCPs into two groups on the basis of their prostate cancer screening practices: "routine screeners" who screened their patients regularly on the basis of their experience and belief in the benefit of PSA screening, and "non-routine screeners" who did not do so because of what they believed to be a lack of scientific evidence documenting the benefit of PSA screening.…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…The study, which included 35 FP physicians and 28 general internists, reported that 79% of PCPs engaged in prescreening discussions with their patients. 10 Our findings also showed that 64.1% (representing 56,137 nationally) of PCPs that engage in discussions reported that their usual policy when discussing PSA testing with patients was to talk the patient into getting the PSA test. In a qualitative study, researchers divided U.S. PCPs into two groups on the basis of their prostate cancer screening practices: "routine screeners" who screened their patients regularly on the basis of their experience and belief in the benefit of PSA screening, and "non-routine screeners" who did not do so because of what they believed to be a lack of scientific evidence documenting the benefit of PSA screening.…”
Section: Resultsmentioning
confidence: 48%
“…15 Factors that have been cited as barriers to physician-patient discussions of prostate cancer screening include lack of time and the complexity of the topic, 14 patient comorbidity, 11 and perception by physicians that the health literacy of their patients is too low for such discussions to be of value. 9 Although some researchers have asked physicians and/or their patients whether they discussed prostate cancer screening, 10,16 the nature of such discussions has not been assessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Guerra et al 23 found that prostate cancer screening discussion occurred in only 36% patient-physician encounters when patients were due for prostate cancer screening. Barriers to discussion were patient comorbidity, limited education/ health literacy, previous refusal of care, physician 24 It is important to note that the goal of this study was not to advocate for the use of PSA screening, whose benefits are still questioned by some. 5,12 It should be recognized, however, that many physicians order PSA routinely for their patients.…”
Section: Discussionmentioning
confidence: 93%
“…3 The facets of the decision remain hard to explain, and many doctors still order PSA blood tests without discussing the possible downsides of screening. 4 Others fail to mention the test at all, setting many of their patients up for a possible surprise, given that 3 % of men under their care will eventually die of prostate cancer. 5 The root of the uncertainty is that prostate cancer is generally a very slow-growing cancer.…”
mentioning
confidence: 99%